Chemical Analysis of Some Herbicides Contents of Most Common Vegetables and Aquatic Animals in Makurdi Metropolis - Anhwange, B.A; Agbaji, E. B; Gimba, C.E; Ajibola, V.O (International Journal of Natural Sciences Research, 2013)
Vegetables, water snails and fish samples were collected from farmlands, river, streams, wetlands, and stagnant waters within Makurdi metropolis and analysed for two common herbicides (2,4-dichlorophenoxyacetic acid (2,4-D) and glyphosate) residues using GC-MS. This was to assess the impact of anthropogenic activities on the samples. The result of the analysis indicate only Tilapia fish (Oreochromis niloticus) to contain about 0.01mgL-1 of 2,4-D acid, while glyphosate was not detected in all the samples. The result of the study revealed that all the samples were free from the two herbicides except Oreochromis niloticus that was contaminated with 2,4-dichlorophenoxyacetic acid. This implies that these activities had not impacted sternly on the surrounding environment; however it is believed that long term exposure may result to some health threat.